Psychedelic psychiatry LSD from clinic to campus - Dyck, Erika 1975- (<<The>> Johns Hopkins University Press, 2008)
"LSD's short but colorful history in North America carries with it the distinct cachet of counterculture and government experimentation. The truth about this mind-altering chemical cocktail is far more complex - and less controversial - than generally believed." "Psychedelic Psychiatry is the tale of medical researchers working to understand LSD's therapeutic properties just as escalating anxieties about drug abuse in modern society laid the groundwork for the end of experimentation at the edge of psychopharmacology. Historian Erika Dyck deftly recasts our understanding of LSD to show it as an experimental substance, a medical treatment, and a tool for exploring psychotic perspectives - as well as a recreational drug. She recounts the inside story of the early days of LSD research in small-town, prairie Canada, when Humphry Osmond and Abram Hoffer claimed incredible advances in treating alcoholism, understanding schizophrenia and other psychoses, and achieving empathy with their patients." "In relating the drug's short, strange trip, Dyck explains how concerns about countercultural trends led to the criminalization of LSD and other so-called psychedelic drugs - opening the way for an explosion in legal prescription pharmaceuticals - and points to the recent re-emergence of sanctioned psychotropic research among psychiatric practitioners. Her challenge to the prevailing wisdom behind drug regulation and addiction therapy provides a historical corrective to our perception of LSD's medical efficacy."--BOOK JACKET.